SINTESIS DAN KARAKTERISASI FT-IR MATERIAL GIANT DIELECTRIC CCTO DENGAN METODE REAKSI PADATAN - Febriana, Siska; Abraha, Kamsul (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Synthesis of giant dielectric material CaCu3Ti4O12, commonly called CCTO, using a solid-state reaction method has been done. The technique includes of mixing, compacting and heating such as calcination and sintering. The three types of starting powders : CaCO3, CuO and TiO2 were mixed then calcinated at 1100 and sintered for different temperatures at 500 , 700 and 900 . The sintered powders were characterized by X-ray diffraction (XRD) for investigate the cristalinity phase, FT-IR spectroscopy and grain size measurement. X-ray diffraction results show that CCTO synthesized with sintering treatment give material a better crystallinity than without using sintering treatment. FT-IR characteristic spectra show the main absorption at wavenumber 447,49 for 500 , 700 and 900 sintered powder that indicate the vibrations of vTi-O-Ti type. Furthermore, the vTi-O type vibrations appear at wavenumber 509,21 and 555,5 ; 516,92 and 570,93 ; 524,64 and 578,64 for 500 , 700 and 900 sintered powder respectively. However, the results of grain size calculation point out that the grain size increases with increasing sintering temperature. Keywords : Solid-state reaction, X-ray diffraction, FT-IR spectroscopy.